2
$\begingroup$

This is Ch 7, Exercise 62 in Palka's Complex Function Theory. Define $$ f:B(0,2 \pi) \to \mathbb{C},z \mapsto \frac{z}{e^z-1}\text{ if }z \neq 0, \; f(0):=1$$ Let $f$ have Taylor series $$f(z)= \sum_{n=0}^\infty \frac{B_n}{n!}z^n$$ where the $B_n$ are Bernoulli numbers (Here I use Wikipedia's notation, not Palka's). The question is to show $$\sum_{k=1}^{n}\binom{2n+1}{2k}B_{2k}= \frac{2n-1}{2}\tag{1}$$ I am stuck on showing this, but have some initial leads (from earlier in the problem). We have $B_0=f(0)=1$, and from Palka's hint, $z \mapsto z/2+f(z)$ is even: $$\begin{split} \frac{z}{2}+f(z)=& \frac{z(e^z-1)+2z}{2(e^z-1)}= \frac{ze^z+z}{2(e^z-1)}\\ \frac{-z}{2}+f(-z)=& \frac{-z}{2}- \frac{ze^z}{1-e^z}= \frac{-z(e^z-1)+2ze^z}{2(e^z-1)}= \frac{ze^z+z}{2(e^z-1)} \end{split}$$ which reveals $B_1=-1/2$ and $B_n=0$ for $n>2$ odd. I have also tried manipulating $(1)$: since $B_1$ is the only nonzero odd Bernoulli number: $$\sum_{k=1}^{2n}\binom{2n+1}{k}B_k= \frac{2n-1}{2}+ \binom{2n+1}{1}B_1=-1$$ or starting the sum at $0$: $$\sum_{k=0}^{2n}\binom{2n+1}{k}B_k=-1+ \binom{2n+1}{0}B_0=0$$ but I didn't get any additional insight on how to show $(1)$. Any help is greatly appreciated.

$\endgroup$
1
$\begingroup$

Hint:

$$(e^z-1)f(z)=z.$$

Differentiating $n$ times,

$$\sum_{k=0}^n\binom nk(e^z-1)^{(n-k)}f^{(k)}(z)=0.$$

Then with $z=0$,

$$\sum_{k=0}^n\binom nkF_k-F_n=0.$$

$\endgroup$
  • $\begingroup$ Thx, I see now how binomial coefficients come out by applying the product rule n times. $\endgroup$ – Jason Mar 20 at 0:13
0
$\begingroup$

Here is a sketch, where I will omit details for you to flesh out. Recall that $\dbinom{n}{k}=\dbinom{n}{n-k}$, and rewrite the sum under consideration as

$$\begin{align*} \sum_{k=1}^{n}\binom{2n+1}{2k}B_{2k}&=\sum_{k=1}^{n}\binom{2n+1}{2n-2k+1}B_{2k}\\ &=\sum_{k=1}^{n}\frac{(2n+1)!}{(2n-2k+1)!}\frac{B_{2k}}{(2k)!}\\ &=-1+\sum_{k=0}^{n}\frac{(2n+1)!}{(2n-2k+1)!}\frac{B_{2k}}{(2k)!} \end{align*}$$

where the last sum should be recognizable as a convolution. Recall that multiplying two power series yields a new power series whose coefficients are a convolution of the coefficients of the two original series, and proceed from there.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.